Differentiating between fertilized and unfertilized eggs prior to incubation based on oxygen flux measurement - Qiaohua, Wang; Dandan, Fu; Meihu, Ma; Tao, Zhang (International Journal of Agricultural and Biological Engineering, 2017)
One unresolved challenge in the egg industry is how to efficiently and non-invasively detect unfertilized eggs prior to incubation. This detection ability would not only significantly improve hatching rates and reduce costs but also conserve incubator space and prevent poor-quality embryos from contributing to the spread of infections. This study demonstrates a procedure for distinguishing between fertilized and unfertilized eggs prior to incubation by studying the respiratory differences between fertilized and unfertilized eggs using the Non-invasive Micro-test Technique (NMT). A customized micro-testing examination platform, NMT Egg Testing System (NMT-ETS) was constructed for the real-time monitoring of the intensity and rate of oxygen exchange between the egg and its external environment. The results from this study revealed that at room temperature, there is a significant difference in gas exchange rates between fertilized and unfertilized eggs. The results indicate that the oxygen flux of fertilized eggs exceed 20 pmol/(cm2•s), whereas unfertilized eggs show a much lower oxygen flux. Based on the results, the NMT method can be used to effectively distinguish between fertilized and unfertilized chicken eggs.Keywords: oxygen flux, gas exchange rates, fertilized eggs, unfertilized eggs, non-invasive micro-test techniqueDOI: 10.25165/j.ijabe.20171004.2606Citation: Wang Q H, Fu D D, Ma M H, Zhang T. Differentiating between fertilized and unfertilized eggs prior to incubation based on oxygen flux measurement. Int J Agric & Biol Eng, 2017; 10(4): 243–251.